Analysis of CuZn5 Tube Buckling During Producing of the Crossover Bend for Metallurgical Unit - Kukhar, V. V.; Povazhnyi, O. S.; Grushko, O.; Кухар, В. В.; Поважний, О. С.; Грушко, О. (International Association for Technological Development and Innovations, 2022)
Crossover bends in metallurgical units are used in pipelines for cooling systems and supplying liquids and gases under pressure. Because of the active placement environment, copper-based thick-walled tubular materials such as brass of the CuZn5 type are used. Due to the small need for crossover bends re- placing, their purchase is impractical, and low-tool methods should be considered for manufacturing. The expansion of the known method for bent axis parts obtained by buckling on the CuZn5 tubular blanks for the metallurgical unit’s crossover bends production is proposed in this paper. The mathematical model for the stress-strain state determination at any point of a CuZn5 tubular blank under buckling has been developed. It is revealed that a Gaussian function is suited to describe the buckled tube shape for crossover bends. Collation of calculated and experimental results showed their satisfactory convergence: for change the blank axis length – 2.08%, for the deflection along the axis line – 15%, for the blank wall thickness – 6%. Dangerous zones have been identified where pipe wall folding can occur at a high upset reduction.